Social History of the Parongpong Tablighi Jamaat (1985-2023) - Hakim, Ajid (TEMALI : Jurnal Pembangunan Sosial, 2024)
There are several interesting things about the Tablighi Jamaah (hereinafter referred to as JT) movement. This interesting phenomenon includes, first, the da'wah method. JT's preaching method is considered unique and contradictory by some laypeople. In his preaching method, it is necessary to leave the family for a certain time. So this method requires members to leave work and family. This, of course, has an impact on the family's livelihood and productivity. Meanwhile, earning a living for the family is considered a sharia obligation. This is the first contradictory and unique condition. However, on the other hand, this co-contradictory condition is followed by other conditions. No method of preaching exceeds the speed carried out by JT. Suddenly, after going out (khuruj) for 3 days, he suddenly became a brother of worship and regretted his sins in the past. This condition of spiritual change certainly cannot be carried out by individuals or other religious organizations. This event only occurs in the JT tradition.